Investigating Human and Social Factors in Requirements Engineering in Software Ecosystems - Gonçalves, Rodrigo Feitosa; Malcher, Paulo; Costa, Luiz Alexandre; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
In software ecosystems (SECO), requirements engineering (RE) activities and process require the collaboration of several stakeholders such as requirements engineers, users, third-party developers, collaborators etc. Therefore, it is a highly human-dependent process. Identifying how human and social factors can influence RE-related activities and process would improve RE in SECO. In this context, this study aims to identify which human and social factors influence RE activities in SECO. To do, we conducted a rapid review, supplemented with the snowballing technique to retrieve published studies. A total of 673 studies were returned, of which 12 were included and analyzed from three research questions that provided us with an understanding of the human and social factors of RE in SECO. The results indicate that decision making, multiple actors, geographic distance/time, and negotiation skills are important human and social factors when involved in RE activities in SECO. Finally, the results of this study can help practitioners and researchers define mechanisms to enhance the positive and decrease the negative influence of these factors.